How to use three-dimensional optical coherence tomography effectively in coronary bifurcation stenting - Murasato, Yoshinobu (Frontiers in Cardiovascular Medicine, 2022)
Imaging-guided coronary bifurcation intervention has improved clinical outcomes due to appropriate size selection of the devices and optimization of the procedure (sufficient stent expansion, reduction of stent malapposition, appropriate stent landing zone, and detection of vessel dissection). In particular, three-dimensional optical coherence tomography (3D OCT) facilitates clear visualization of stent configuration and guidewire position, which promotes optimal guidewire crossing to the side branch. Successive side branch dilation leads to wide ostial dilation with less strut malapposition. However, the link connection of the stent located on the bifurcated carina has been found to be an obstacle for sufficient opening of the side branch, which results in incomplete strut apposition. In such cases, the aggressive proximal optimization technique improves the jailing strut pattern, and 3D OCT navigates the guidewire crossing to the optimal cell that is most likely to be expanded sufficiently, which is not always a distal cell. In two-stent deployment, 3D OCT facilitates optimal guidewire crossing, which leads to less metallic carina, clustering, and overlapping. The present review describes a method of clear visualization and assessment with 3D OCT and discusses the efficacy of 3D OCT in coronary bifurcation stenting in clinical practice.